IL-1β suppresses innate IL-25 and IL-33 production and maintains helminth chronicity. - Mario M Zaiss; Kendle M Maslowski; Ilaria Mosconi; Nadine Guenat; Benjamin J Marsland; Nicola L Harris (PLoS Pathogens)
Approximately 2 billion people currently suffer from intestinal helminth infections, which are typically chronic in nature and result in growth retardation, vitamin A deficiency, anemia and poor cognitive function. Such chronicity results from co-evolution between helminths and their mammalian hosts; however, the molecular mechanisms by which these organisms avert immune rejection are not clear. We have found that the natural murine helminth, Heligmosomoides polygyrus bakeri (Hp) elicits the secretion of IL-1β in vivo and in vitro and that this cytokine is critical for shaping a mucosal environment suited to helminth chronicity. Indeed in mice deficient for IL-1β (IL-1β(-/-)), or treated with the soluble IL-1βR antagonist, Anakinra, helminth infection results in enhanced type 2 immunity and accelerated parasite expulsion. IL-1β acts to decrease production of IL-25 and IL-33 at early time points following infection and parasite rejection was determined to require IL-25. Taken together, these data indicate that Hp promotes the release of host-derived IL-1β that suppresses the release of innate cytokines, resulting in suboptimal type 2 immunity and allowing pathogen chronicity.